2004
DOI: 10.1242/dev.01277
|View full text |Cite
|
Sign up to set email alerts
|

Repression of the vertebrate organizer by Wnt8 is mediated by Vent and Vox

Abstract: Dorsoventral (DV) patterning of vertebrate embryos requires the concerted action of the Bone MorphogeneticProtein (BMP) and Wnt signaling pathways. In contrast to our understanding of the role of BMP in establishing ventral fates, our understanding of the role of Wnts in ventralizing embryos is less complete. Wnt8 is required for ventral patterning in both Xenopus and zebrafish; however, its mechanism of action remains unclear. We have used the zebrafish to address the requirement for Wnt8 in restricting the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
136
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 102 publications
(147 citation statements)
references
References 45 publications
8
136
2
1
Order By: Relevance
“…Additionally, while over-expression of BMP at moderate levels was found to induce wnt8 expression, high levels of BMP repress wnt8, suggesting the induction of wnt8 in response to BMP is under complex regulation (Marom et al, 1999). In zebrafish, it has been reported that Wnt8 over-expression can induce ectopic bmp2b (Agathon et al, 2003), but BMP is not necessary for normal wnt8 expression (Mullins, 1999;Ramel and Lekven, 2004;Szeto and Kimelman, 2004), suggesting an alternate transcriptional relationship in zebrafish. However, analysis of swr mutants suggests that high BMP activity can negatively regulate wnt8 at the end of gastrulation (Hammerschmidt and Mullins, 2002), similar to the relationship observed in amphibians.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, while over-expression of BMP at moderate levels was found to induce wnt8 expression, high levels of BMP repress wnt8, suggesting the induction of wnt8 in response to BMP is under complex regulation (Marom et al, 1999). In zebrafish, it has been reported that Wnt8 over-expression can induce ectopic bmp2b (Agathon et al, 2003), but BMP is not necessary for normal wnt8 expression (Mullins, 1999;Ramel and Lekven, 2004;Szeto and Kimelman, 2004), suggesting an alternate transcriptional relationship in zebrafish. However, analysis of swr mutants suggests that high BMP activity can negatively regulate wnt8 at the end of gastrulation (Hammerschmidt and Mullins, 2002), similar to the relationship observed in amphibians.…”
Section: Introductionmentioning
confidence: 99%
“…Wnt and BMP activities can activate ventral genes independently of each other, but they also share some common targets (Hoppler and Moon, 1998;Marom et al, 1999;Ramel and Lekven, 2004;Szeto and Kimelman, 2004). While studies in zebrafish have highlighted a dynamic regulation of target genes by both pathways (Ramel and Lekven, 2004), it is still unclear what their relationship is: work in several model systems has shown that their relationship is complex and may involve cross-regulatory interactions at multiple levels (Hoppler and Moon, 1998;Marom et al, 1999;Fuentealba et al, 2007). Understanding the individual roles of Wnt and BMP signaling is critical for deciphering the regulation of vertebrate D/V patterning.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations